2006
DOI: 10.1007/s10915-005-9062-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Tubular Grid: An Efficient Data Structure and Algorithms for High Resolution Level Sets

Abstract: Level set methods [Osher and Sethian. Fronts propagating with curvaturedependent speed: algorithms based on Hamilton-Jacobi formulations. J. Comput. Phys. 79 (1988) 12] have proved very successful for interface tracking in many different areas of computational science. However, current level set methods are limited by a poor balance between computational efficiency and storage requirements. Tree-based methods have relatively slow access times, whereas narrow band schemes lead to very large memory footprints f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 37 publications
0
92
0
Order By: Relevance
“…We also mention that other local level-set methods have been proposed, see e.g [105,99,72] and the references therein. Finally, we note that true local-level-set methods, i.e.…”
Section: Improvement On Mass Conservationmentioning
confidence: 99%
“…We also mention that other local level-set methods have been proposed, see e.g [105,99,72] and the references therein. Finally, we note that true local-level-set methods, i.e.…”
Section: Improvement On Mass Conservationmentioning
confidence: 99%
“…Therefore, unlike other state-of-theart CPU methods (e.g. [11], [25]), our method is limited in the maximum resolution that can be achieved, by the (relatively small) amount of memory available on mainstream GPUs. However, in terms of GPU level sets, resolutions of 4096 3 voxels have not previously been achieved.…”
Section: E Discussion and Limitationsmentioning
confidence: 99%
“…Recently, Nielsen and Museth introduced the "Dynamic Tubular Grid" (DT-Grid) [25], a recursive, compressed levelset representation inspired by the compressed-row-storage technique used to represent sparse matrices. They showed that the memory requirement of DT-Grid is optimal, i.e., it is proportional to the size of the interface.…”
Section: Sparse Cpu Methodsmentioning
confidence: 99%
See 2 more Smart Citations